2015
DOI: 10.2147/iprp.s72206
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist interventions for obesity: improving treatment adherence and patient outcomes

Abstract: Obesity is currently a worldwide pandemic, with overweight (body mass index [BMI] ≥25 kg/m2) and obesity (BMI ≥30 kg/m2) estimated at 35% and 12% of the global adult population, respectively. According to data collected from the United States National Health and Nutrition Examination Survey, approximately 68.8% of US adults are overweight or obese. Additionally, a large burden of health care costs can be attributed directly to obesity as well as multiple, potentially preventable, comorbidities such as cancer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 57 publications
(60 reference statements)
1
42
0
4
Order By: Relevance
“…However, in the UK, only a small number of studies exist in terms of the evaluation and success rate of pharmacy-led WM services. Most of the studies, even those with high dropout rates, concluded that pharmacy-led WM services can have a potential positive effect in weight-loss management and lifestyle alterations [7]. Boardman et al [8] assessed the success rate of such services in supporting obese patients during weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the UK, only a small number of studies exist in terms of the evaluation and success rate of pharmacy-led WM services. Most of the studies, even those with high dropout rates, concluded that pharmacy-led WM services can have a potential positive effect in weight-loss management and lifestyle alterations [7]. Boardman et al [8] assessed the success rate of such services in supporting obese patients during weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…The WHO estimated that in 2016 more than 1.9 billion adults were overweight (nearly 40% of the population) and over 650 million (13% of the population) were people with obesity [107].Globally, the annual cost of obesity-related diseases has reached $2 trillion according to a recent report by McKinsey Global Institute [108]. Obesity increases cardiovascular risk through risk factors such as increased fasting plasma triglycerides, high LDL cholesterol, low HDL cholesterol, elevated blood glucose and insulin levels and high blood pressure [109,110]. Also, obesity causes cerebral vasculopathy, gallbladder lithiasis, arthropathy, ovarian polycytosis, sleep apnea syndrome, and some neoplasms [111].…”
Section: Obesity Managementmentioning
confidence: 99%
“…Moreover, the Accreditation Council for Pharmacy Education (ACPE) Standards requires pharmacists be trained to interpret laboratory results, perform health screenings, and provide basic physical assessments [23]. Pharmacists also learn how to design and implement national or community-based public health, wellness, and prevention programs [23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Accreditation Council for Pharmacy Education (ACPE) Standards requires pharmacists be trained to interpret laboratory results, perform health screenings, and provide basic physical assessments [23]. Pharmacists also learn how to design and implement national or community-based public health, wellness, and prevention programs [23]. This baseline knowledge can be easily paired with specific training on basic dietary counselling, physical activity guidance, and behavioral counseling prior to providing a weight management program [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation